Effects of rGO incorporation on structural and magnetic properties of Ni-Zn ferrite nanostructures - Nag, Sanchayita; Roychowdhury, Anirban; Das, Dipankar; Mukherjee, Sampad (Journal of magnetism and magnetic materials, 2022)
•CTAB assisted synthesis of Ni0.5Zn0.5Fe2O4/rGO nano hybrid by sol–gel auto-combustion.•Super paramagnetic relaxation as well as presence of two ordered magnetic sites.•Evolution of one doublet and two sextets in the hyperfine spectra.•Enhanced surface spin disorder: enhancement in coercivity. Ni0.5Zn0.5Fe2O4 (NZ)/reduced graphene oxide (rGO) nanohybrids were prepared by surfactant assisted citric acid mediated sol–gel auto combustion method. Samples were analyzed by various characterization techniques to acquire information about the structural, morphological, thermal and magnetic properties. X-ray diffraction results confirm the successful synthesis of NZ/rGO nanocomposite. Transmission electron microscopic images reveal that the NZ nanostructures are well decorated on the rGO matrix. Few of them are also sandwiched within the rGO sheets. Samples were thermally characterized by thermo-gravimetric setup. Raman spectroscopic technique was also employed for the analysis of the samples. The room temperature Mössbauer spectra of the samples were fitted into a doublet and two sextets owing to the presence of two magnetic sites. Room temperature (300 K), as well as low temperature (10 K) M−H loops of the samples were recorded by SQUID magnetometer. Enhancement in the value of coercivity of the NZ/rGO sample with comparison to the pure NZ, has established that the incorporation of rGO has effectively influenced the magnetic property of pure NZ.